Analisis Strategi Etika Bisnis Agensi Hiburan Korea Selatan dalam Menghadapi Fenomena Cancel Culture - Tariza Mega Pratiwi Garini; Halimah Zahrah; Aulia Silvana; Haura Nurul Ilmi; Naura Rahadhatul Aisy (Teewan Journal Solutions, 2025)
This study explores the ethical business strategies of South Korean entertainment agencies in responding to the growing challenge of cancel culture within the entertainment industry. In a landscape highly sensitive to public morality, the reputations of both artist and agencies can collapse under intense ethical scrutiny. Using a qualitative case study approach, the research collects data from official agency statements, media reports, and public reactions. Findings reveal that agencies often prioritize the company’s and group’s image over individual artists, especially in cases involving legal or moral violations. Speed, transparency, and sincerity in responses can worsen the crisis. The study analyzes notable cases such as B.I’s (Kim Hanbin) drug allegations, bullying controversies involving Kim Garam and Jimin , and scandals linked to Kim Seon-ho and Kim Sae-ron. Results indicate that although the impact on artists’ careers can be severe and long-term, rehabilitation remains possible-as seen in Kim Seon-ho’s case. This research provides valuable insights into reputation management dynamics and ethical pressures within South Korea’s highly public and competitive entertainment culture.